Extracellular Vesicles Role in Diseases, Pathogenesis and Therapy - Paul, Manash K. (Physiology, 2022)
Extracellular vesicles (EVs) are nanoscale vesicles secreted by cells that mediate horizontal cargo transport from donor to recipient cell, thereby establishing cell-cell communication and signaling. This book provides critical information on the fundamentals of EVs, their roles in diseases like cancer, and their use in disease management. The chapters emphasize the emerging data confirming the role of EVs in the pathogenesis of diseases and discuss the scientific advances that have made it feasible to characterize and engineer EVs, leading to their use as tools in biomarker discovery and disease diagnosis, prognosis, therapeutic application, and theranostics. This volume is a valuable resource for basic biologists, translational scientists, and clinicians.